Effect of coronary flow on intracoronary alteplase: a prespecified analysis from a randomised trial. Issue 4 (12th January 2021) - Maznyczka, Annette Marie; McCartney, Peter; Duklas, Patrycja; McEntegart, Margaret; Oldroyd, Keith G; Greenwood, John P; Muir, Douglas; Chowdhary, Saqib; Gershlick, Anthony H; Appleby, Clare; Eteiba, Hany; Cotton, James; et al.
Abstract : Objectives: Persistently impaired culprit artery flow (<TIMI 3) during primary percutaneous coronary intervention is a surrogate for failed myocardial perfusion. We evaluated the effects of intracoronary alteplase according to TIMI flow grade immediately preceding drug administration. Methods: In T-TIME (trial of low-dose adjunctive alTeplase during primary PCI), patients ≤6 hours from onset of ST-elevation myocardial infarction (STEMI) were randomised to placebo, alteplase 10 mg or alteplase 20 mg, administered by infusion into the culprit artery, pre-stenting. In this prespecified, secondary analysis, coronary flow was assessed angiographically at the point immediately before drug administration. Microvascular obstruction, myocardial haemorrhage and infarct size were assessed by cardiovascular magnetic resonance (CMR) at 2–7 days and 3 months. Results: TIMI flow was assessed after first treatment (balloon angioplasty/aspiration thrombectomy), immediately pre-drug administration, in 421 participants (mean age 61±10 years, 85% male) and was 3, 2 or 1 in 267, 134 and 19 participants respectively. In patients with TIMI flow ≤2 pre-drug, there was higher incidence of microvascular obstruction with alteplase (alteplase 20 mg (53.1%) and 10 mg (59.5%) combined versus placebo (34.1%); OR=2.47 (95% CI 1.16 to 5.22, p=0.018) interaction p=0.005) and higher incidence of myocardial haemorrhage (alteplase 20 mg (53.1%) and 10 mg (57.9%) combined vs placebo (27.5%); OR=3.26 (95% CI 1.44 to 7.36, p=0.004) interaction p=0.001). These effects were not observed in participants with TIMI 3 flow pre-drug. There were no interactions between TIMI flow pre-drug, alteplase and 3-month CMR findings. Conclusion: In patients with impaired culprit artery flow (<TIMI 3) after initial balloon angioplasty/thrombus aspiration, intracoronary alteplase was associated with increased presence of microvascular obstruction and myocardial haemorrhage. Trial registration number: NCT02257294 .